Factors associated with severe maternal morbidity in Kelantan, Malaysia: A comparative cross-sectional study. Issue 1 (December 2016) - Norhayati, Mohd Noor; Nik Hazlina, Nik Hussain; Aniza, Abd. Aziz; Sulaiman, Zaharah
Abstract Background Knowledge on the factors associated with severe maternal morbidity enables a better understanding of the problem and serves as a foundation for the development of an effective preventive strategy. However, various definitions of severe maternal morbidity have been applied, leading to inconsistencies between studies. The objective of this study was to identify the sociodemographic characteristics, medical and gynaecological history, past and present obstetric performance and the provision of health care services as associated factors for severe maternal morbidity in Kelantan, Malaysia. Methods A comparative cross-sectional study was conducted in two tertiary referral hospitals in 2014. Postpartum women with severe morbidity and without severe morbidity who fulfilled the inclusion and exclusion criteria were eligible as cases and controls, respectively. The study population included all postpartum women regardless of their age. Pregnancy at less than 22 weeks of gestation, more than 42 days after the termination of pregnancy and non-Malaysian citizens were excluded. Consecutive sampling was applied for the selection of cases and for each case identified, one unmatched control from the same hospital was selected using computer-based simple random sampling. Simple and multiple logistic regressions were performed using Stata Intercooled version 11.0. Results A total of 23, 422 pregnant women were admitted to these hospitals in 2014 and 395 women with severe maternal morbidity were identified, of which 353 were eligible as cases. An age of 35 or more years old [Adj.OR (95 % CI): 2.6 (1.67, 4.07)], women with past pregnancy complications [Adj.OR (95 % CI): 1.7 (1.00, 2.79)], underwent caesarean section deliveries [Adj.OR (95 % CI): 6.8 (4.68, 10.01)], preterm delivery [Adj.OR (95 % CI): 3.4 (1.87, 6.32)] and referral to tertiary centres [Adj.OR (95 % CI): 2.7 (1.87, 3.97)] were significant associated factors for severe maternal morbidity. Conclusions Our study suggests the enhanced screening and monitoring of women of advanced maternal age, women with past pregnancy complications, those who underwent caesarean section deliveries, those who delivered preterm and the mothers referred to tertiary centres as they are at increased risk of severe maternal morbidity. Identifying these factors may contribute to specific and targeted strategies aimed at tackling the issues related to maternal morbidity.